Genetic risk score is associated with T2DM and diabetes complications risks - Hubacek, Jaroslav A; Dlouha, Lucie; Adamkova, Vera; Dlouha, Dana; Pacal, Lukas; Kankova, Katerina; Galuska, David; Lanska, Vera; Veleba, Jiri; Pelikanova, Terezie (Gene, 2023)
BACKGROUND: Type 2 diabetes mellitus (T2DM) is a prototypical complex disease with polygenic architecture playing an important role in determining susceptibility to develop the disease (and its complications) in subjects exposed to modifiable lifestyle factors. A current challenge is to quantify the degree of the individual's genetic risk using genetic risk scores (GRS) capturing the results of genome-wide association studies while incorporating possible ethnicity- or population-specific differences. METHODS: This study included three groups of T2DM (T2DM-I, N = 1,032; T2DM-II, N = 353; and T2DM-III, N = 399) patients and 2,481 diabetes-free subjects. The status of the microvascular and macrovascular diabetes complications were known for the T2DM-I patients. Overall, 21 single nucleotide polymorphisms (SNPs) were analyzed, and selected subsets were used to determine the GRS (both weighted - wGRS and unweighted - uGRS) for T2DM risk predictions (6 SNPs) and for predicting the risks of complications (7 SNPs). RESULTS: The strongest T2DM markers (P < 0.0001) were within the genes for TCF7L2 (transcription factor 7-like 2), FTO (fat mass and obesity associated protein) and ARAP1 (ankyrin repeat and PH domain 1). The T2DM-I subjects with uGRS values greater (Odds Ratio, 95 % Confidence Interval) than six had at least twice (2.00, 1.72-2.32) the risk of T2DM development (P < 0.0001), and these results were confirmed in the independent groups (T2DM-II 1.82, 1.45-2.27; T2DM-III 2.63, 2.11-3.27). The wGRS (>0.6) further improved (P < 0.000001) the risk estimations for all three T2DM groups. The uGRS was also a significant predictor of neuropathy (P < 0.0001), nephropathy (P < 0.005) and leg ischemia (P < 0.0005). CONCLUSIONS: If carefully selected and specified, GRS, both weighted and unweighted, could be significant predictors of T2DM development, as well as the diabetes complications development.
Keywords: celogenomová asociační studie; Polymorphism, Single Nucleotide; Humans; Polymorphism; jednonukleotidový polymorfismus; rizikové faktory; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; T-buňky - transkripční faktor 1; lidé; Diabetes Mellitus, Type 2; Diabetes; T Cell Transcription Factor 1; komplikace diabetu; Diabetes Complications; Genetic Predisposition to Disease; genetická predispozice k nemoci; Genome-Wide Association Study; gen pro FTO; Complications; diabetes mellitus 2. typu; Gene score; Risk Factors